(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
One of the most important and recurring debates in the field of International Political Economy and international affairs are the links between capitalism, fossil fuel energy and climate change (Ajl 2021; Albert 2020; Brand and Wissen 2018; Daggett 2019; Di Muzio 2015; Di Muzio and Dow 2022; Gill and Benetar 2020; Goods 2021; Kuzemko et al 2019; Malm 2016; Newell 2021; Newell and Lane 2017; Paterson 2021; Pirani 2018; Siebert 2020;). 1 In these debates, the origins of our current climate emergency is rooted in how Britain became the first country to become reliant on mass production and consumption coal (fossil fuels) for economic growth, industrialization, as well as social reproduction (Di Muzio 2015; Malm 2016; Moore 2015; ADD OTHER FELLA). Britain becoming a coal-fire capitalist-imperial global empire deeply influenced and structured the current world order and global political economy which is still locked-into a vicious cycle of path dependency whereby balance of power, production and social reproduction is dependent on energy, predominately fossil fuels (Di Muzio and Dow 2022). This article offers a critical politicaleconomy engagement not on the origins of climate emergency but on the explanation as to why Britain turned to fossil fuels in the first place. The scope of scholarship is plentiful but can generally be framed into two dominant perspectives. The first comes from what can be called the Malthusian or Neoclassical Economics explanation whereby Britain was forced to transition to coal from previous sources of energy (wind, peat, timber, etc.) because of resource scarcities, predominately timber, and thereby raising commodity and labour prices (CITE).